Heat exposure and cardiovascular health outcomes: a systematic review and meta-analysis. Issue 6 (June 2022) - Liu, Jingwen; Varghese, Blesson M; Hansen, Alana; Zhang, Ying; Driscoll, Timothy; Morgan, Geoffrey; Dear, Keith; Gourley, Michelle; Capon, Anthony; Bi, Peng
Summary: Background: Heat exposure is an important but underappreciated risk factor contributing to cardiovascular disease. Warming temperatures might therefore pose substantial challenges to population health, especially in a rapidly aging population. To address a potential increase in the burden of cardiovascular disease, a better understanding of the effects of ambient heat on different types of cardiovascular disease and factors contributing to vulnerability is required, especially in the context of climate change. This study reviews the current epidemiological evidence linking heat exposures (both high temperatures and heatwaves) with cardiovascular disease outcomes, including mortality and morbidity. Methods: In this systematic review and meta-analysis, we searched PubMed, Embase, and Scopus for literature published between Jan 1, 1990, and March 10, 2022, and evaluated the quality of the evidence following the Navigation Guide Criteria. We included original research on independent study populations in which the exposure metric was high temperatures or heatwaves, and observational studies using ecological time series, case crossover, or case series study designs comparing risks over different exposures or time periods. Reviews, commentaries, grey literature, and studies that examined only seasonal effects without explicitly considering temperature were excluded. The risk estimates were derived from included articles and if insufficient data were available we contacted the authors to provide clarification. We did a random-effects meta-analysis to pool the relative risk (RR) of the association between high temperatures and heatwaves and cardiovascular disease outcomes. The study protocol was registered with PROSPERO (CRD42021232601). Findings: In total, 7360 results were returned from our search of which we included 282 articles in the systematic review, and of which 266 were eligible for the meta-analysis. There was substantial heterogeneity for both mortality (high temperatures: I 2 =93·6%, p<0·0001; heatwaves: I 2 =98·9%, p<0·0001) and morbidity (high temperatures: I 2 =98·8%, p<0·0001; heatwaves: I 2 =83·5%, p<0·0001). Despite the heterogeneity in environmental conditions and population dynamics among the reviewed studies, results showed that a 1°C increase in temperature was positively associated with cardiovascular disease-related mortality across all considered diagnoses. The overall risk of cardiovascular disease-related mortality increased by 2·1% (RR 1·021 [95%CI 1·020–1·023]), with the highest specific disease risk being for stroke and coronary heart disease. A 1°C temperature rise was also associated with a significant increase in morbidity due to arrhythmias and cardiac arrest and coronary heart disease. Our findings suggest heat exposure leads to elevated risk of morbidity and mortality for women, people 65 years and older, individuals living in tropical climates, and those in countries of lower-middle income. Heatwaves were also significantly associated with a 17% increase in risk of mortality (RR 1·117 [95% CI 1·093–1·141]), and increasing heatwave intensity with an increasing risk (RR 1·067 [95% CI 1·056–1·078] for low intensity, 1·088 [1·058–1·119] for middle intensity, and 1·189 [1·109–1·269] for high intensity settings). Interpretation: This review strengthens the evidence on the increase in cardiovascular disease risk due to ambient heat exposures in different climate zones. The widespread prevalence of exposure to hot temperatures, in conjunction with an increase in the proportion of older people in the population, might result in a rise in poor cardiovascular disease health outcomes associated with a warming climate. Evidence-based prevention measures are needed to attenuate peaks in cardiovascular events during hot spells, thereby lowering the worldwide total heat-related burden of cardiovascular disease-related morbidity and death. Funding: Australian Research Council Discovery Program.